Investigation of anaphylactic shock caused by bee or wasp stings based on the determination of tryptase enzyme and bee or wasp venom specific immunoglobulin E levels in blood, in certain extraordinary fatal cases (Academic Journal of Internal Affairs, 2024)
Aim: Systemic allergic reactions triggered by bee and wasp venom affect approximately 3% of adults, and in severe cases, can lead to anaphylactic reactions and death. The exact cause of extraordinary deaths resulting from insect stings is often not determined in a significant number of cases. The aim of this study is to provide guidance through methodological recommendations to investigate the precise cause of deaths presumably resulting from insect stings, specifically focusing on uncovering the facts and causes of anaphylaxis.Methodology: The study reviews literature related to anaphylaxis caused by insect stings and animal toxins, as well as its immunological background. It seeks to translate the information found in the literature into the realm of official activities related to extraordinary deaths. The study also summarises knowledge about groups of animals in Hungary that are medically significant due to their venom, providing guidance for on-site recognition, search, documentation, and recording of the most common Hymenoptera species with venom capable of frequently inducing anaphylactic reactions.Findings: The key to diagnosing deaths caused by anaphylaxis lies in crime scene investigation. The attending medical doctor must recognise the symptoms of insect stings and ensure the collection of a blood sample for allergological purposes. A special blood collection kit has been assembled for this purpose. The blood sample, which must be stored at 2–8ºC, should be sent to the Semmelweis University Institute of Laboratory Medicine within 2 days. By measuring the level of tryptase enzyme in the blood sample and detecting the presence of specific immunoglobulin E for the venom of the respective bee or wasp species, the cause of the anaphylactic reaction can be confirmed. The crime scene investigation team should also make an effort to locate and secure the potential insect species responsible for the sting. If the forensic entomologist successfully identifies the species, it facilitates the specific IgE allergological examination for the respective venom.Value: In cases of death resulting from insect stings, the cause is often not determined due to lack of proper caution and appropriate methods. The procedural approach recommended in the study establishes the basis for determining the precise cause of death in cases of suspected insect stings.
Keywords: bee and wasp venom, anaphylactic reaction, extraordinary death, tryptase level